Pengaruh Kualitas Pelayanan Jasa Asuransi Terhadap Tingkat Kepuasan Masyarakat di PT. Jasa Raharja KPJR Pangkalan Balai - Yunita Hasrina (Program Studi Magister Manajemen FE Unsri, 2018)
Tujuan penelitian -. This study aims to identify and analyze influence the quality of insurance services to the level of community satisfaction at PT. Jasa Raharja KPJR Pangkalan BalaiDesain penelitian – The variables used in this study is quality services and level of satisfaction.The analytic technique used in this research is validity test, descriptive analysis, t test analysis, and regression analysisTemuan – Service quality significantly influence the level of community satisfaction at PT. Jasa Raharja KPJR Pangkalan Balai, because the magnitude of the significance value of 0,00 is much smaller than 0,05, so that between service quality and community satisfaction has asignificant relationship.Keterbatasan penelitian -.